Mulheres na contabilidade: os estereótipos socialmente construídos sobre a contadora - Silva, Derley Junior Miranda (2018)
In this study, we investigated the perception of accounting professionals regarding the stereotypes associated with the woman accountant and the accounting profession. To conduct the research, classified as exploratory and descriptive, with a predominantly quantitative approach, a survey was carried out, with survey of professionals of both genera of the city of Uberlândia, in Minas Gerais, who had an active registry in the Regional Accounting Council of Minas Gerais (CRCMG), totaling an accesibility and non-probabilistic sample of 308 (three hundred and eight) accounting professionals. The sociodemographic information of the respondents and the gender stereotypes attributed by them to the accounting profession and to the woman accountant were collected through a questionnaire using adjectives in a Semantic Differential Scale. It should be emphasized that in Block 2 and Block 3 of the research instrument were adaptad the assertions used in the questionnaire of Saemann and Crooker (1999) and Gomes (2009), respectively, both composed by opposing pairs of adjectives in which the respondent is invited to respond on the basis of perception which has on the object searched, through answers elaborated in scale of semantic differential. For the analysis, descriptive statistical resources were used, as well as the Test of Hypotheses for Proportion Difference in order to show differences in the proportions in which the genders perceive the stereotypes found. Both null hypotheses were rejected (H0a and H0b), and it is not possible to affirm that there is no difference in the proportion of the stereotyping of the accounting profession for accountants and accountants, since differences in the proportions of stereotyping of the accounting profession between the respondents of both the genres for flexible stereotypes, people-oriented and imaginative. Regarding the woman accountant, there were differences in the proportions for the stereotypes: leader, practical, independent, confident, with a sense of humor, knowledgeable about business and sensitive reality. Although most accountants have claimed that there are differences between genders in the accounting profession, it has been realized how these gender differences can go unnoticed in the eyes of male accountants. Only 9.8% of the accountants participating in the survey recognize some distance between salary levels, employability and occupation of positions and functions, between accountants and accountants, in the labor market. Even if the perception of the woman accountant has changed, the results obtained in this research point out, especially in relation to negative stereotypes about the image of the woman accountant (bad tempered, imaginative, submissive, better prepared for repetitive activities, antisocial and assuming leadership, realistic, sociable, honest and honest), there still seem to be difficulties, especially in the perception of women themselves, that prevent them from standing out in the corporate environment.